Evaluation of the tourist perception of the spectator in an eSport event - Vegara-Ferri, José Miguel; Ibáñez-Ortega, Diego; Carboneros, María; López-Gullón, José María; Angosto, Salvador (PUBLICACIONES, 2020)
eSports events are a great tourist attraction for event organizations, for this reason, the objective of the study is to analyse the tourist impact of the eSports event “Iberian Cup 2019”. The sample consisted of 390 participants who attended the tournament in the city of Barcelona. The instrument used was a questionnaire that analyses the tourism impact in sport events. In relation to the results, the variables “Emotion-Environment” obtained a greater correlation and the variable “personal of the event” was the best evaluated. The attendees had a good satisfaction of the event and future intentions, being the intention to return in the future to the city of Barcelona the best valued item. Finally, the attendees who did physical activity valued most of the parameters analysed better, finding significant differences between the group that does not do physical activity. These results are useful to create strategies to attract more tourists in future events.